Análisis de la aplicación de coeficientes en las determinaciones presuntivas a personas naturales en la Zonal 8 en el periodo 2011-2012 - Infantes Mantilla, Andrea Viviana (2015)
At least 10 years ago, Ecuador has become a country that represents great expectations and economic interest of the world community, not only from investment opportunities, but on policy and continuous changes to financial and economic level have accomplished. These changes have influenced directly in the tax policies of the country, promoting the increase of the tax burden year after year, through incentive policies, promotion, management and taxation. The proposed herein, discussion is based on the results of performing a presumptive respect of income earned by individuals determination. Tax administration, has among other powers to determine the taxpayer in order to establish the existence of the operative event, the obligor, the tax base and the amount of the tax, this includes, verification, supplementation or amendment of declarations taxpayers or responsible; the composition of the corresponding tax, when the existence of taxable transactions and the adoption of legal measures that may be appropriate to warn that determination. However, there are some causes that may lead to the tax administration to make a presumptive determination given that the tax assessment starts directly. The presumptive determination can be performed in two ways, either exhausting all resources to obtain a more or less certain income, or by applying coefficients estimated presumptive determination thereof that are published by order for each year by the Director General Internal Revenue Service. In this analysis because the database used consists of determinations already completed, the tax base that would result from the application of the coefficients of presumptive estimate of the income declared by natural persons in the period from 2011 is calculated -2012, after obtaining the tax base Caused income tax is calculated and the resulting variation in the tax burden it to estimate the coefficients is analyzed, also noting that it is not an imperative factor in making a determination presumptive economic activity of the taxpayer.